Effect of Work Motivation and Job Satisfaction on Employee Performance (Case study at Islamic bank of BJB Jakarta) - Zaman, Rifki Aliansyah; Zulganef, Zulganef (iora, 2023)
This study was conducted to examine a variety of variables, including work motivation (X1) and job satisfaction (X2), that theoretically have an impact on employee performance (Y). The purpose of this study was to identify and analyze the relationships between work motivation, job satisfaction, and employee performance at the Islamic bank Of BJB Jakarta. It also aimed to determine and analyze the partial and simultaneous effects of work motivation and job satisfaction on employee performance. A saturated sample of 55 employees was used in this study. The research methodology combines a quantitative approach with descriptive and verification methods. The analysis uses Structural Equation Modeling (SEM) analysis, which is based on variance, namely Partial Least Squares (PLS). Based on the research results, the variable of work motivation is included in the